Pengaruh Kualitas Kehidupan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening - Setiyadi, Yusuf Wildan; Wartini, Sri; Wijayanto, Andhi (Management Analysis Journal, 2016)
Decreased levels of employee performance of sales in the last year, among 1.1 % on a special performance and employee absenteeism rate target of 1% is not achievable indicate satisfaction and quality of life of employees can affect employee performance. The problem in this research is there any influence of the quality of work life , job satisfaction on employee performance. The population in this study were all employees of Honda Semarang Center Setiabudi 521 people with a sample of 84 people using the formula Slovin. Methods of data collection using questionnaires, methods of analysis, test instrument (validity and reliability test), descriptive analysis of the percentage, the classic assumption test, multiple regression analysis and path analysis. The results showed that the variable quality of worklife positive effect on job satisfaction; the variable quality of working life has positive influence on employee performance; variable job satisfaction has positive influence on employee performance; and the variable quality of working life through the indirect effect of job satisfaction on employee performance. Suggestions for the company in improving the performance of employees in order to pay attention to aspects of quality of work life and job satisfaction of employees proved influential on employee performance.